Gibljive besede-podobe - Strehovec, Janez (Primerjalna književnost, 2014)
Projects of electronic animated literature intersect the e-literary and the field of moving images, which implies the application of the cinematic and video procedures in the field of digital textuality. This article addresses the moving words-images as the basic units of animated e-literary texts that are also organized with regard to spatial and temporal grammar.
Keywords: književnost in novi mediji; elektronska književnost; video; medmrežje; vmesnik; bralna kultura